2016
DOI: 10.1111/1744-7917.12380
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of coinfection with protective symbionts on the host phenotype and symbiont titres in the pea aphid system

Abstract: Symbiotic associations between microbes and insects are widespread, and it is frequent that several symbionts share the same host individual. Hence, interactions can occur between these symbionts, influencing their respective abundance within the host with consequences on its phenotype. Here, we investigate the effects of multiple infections in the pea aphid, Acyrthosiphon pisum, which is the host of an obligatory and several facultative symbionts. In particular, we study the influence of a coinfection with 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…In the field it is estimated that aphids, for instance, host 0-4 symbionts per individual (Ferrari et al 2012; Russell et al 2013; Smith et al 2015; Zytynska et al 2016), and that multiple infections are particularly common in some genus like Macrosiphum (Henry et al 2015). More importantly, where symbiont co-infections occur strong fitness costs are often observed (Oliver, Moran & Hunter 2006; Guay et al 2009; Leclair et al 2017; McLean et al 2018). It would be very interesting to test this across different aphid species, asking whether the proportion of multiple infections correlates negatively with the fitness costs they impose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field it is estimated that aphids, for instance, host 0-4 symbionts per individual (Ferrari et al 2012; Russell et al 2013; Smith et al 2015; Zytynska et al 2016), and that multiple infections are particularly common in some genus like Macrosiphum (Henry et al 2015). More importantly, where symbiont co-infections occur strong fitness costs are often observed (Oliver, Moran & Hunter 2006; Guay et al 2009; Leclair et al 2017; McLean et al 2018). It would be very interesting to test this across different aphid species, asking whether the proportion of multiple infections correlates negatively with the fitness costs they impose.…”
Section: Discussionmentioning
confidence: 99%
“…While aphid symbionts are predominantly vertically transmitted from mother to offspring, there is also evidence of horizontal transfer of symbionts among aphids during sexual reproduction (Moran & Dunbar 2006), by parasitoids when ovipositing eggs into aphids (Gehrer & Vorburger 2012), or even through infected honeydew (Darby & Douglas 2003). Based on a few laboratory studies, aphid hosts impose little constrains to symbiont acquisition even if the host already carries a facultative symbiont, demonstrated by successful microinjecting of different symbiont species and strains into pea aphids (Leclair et al 2017; McLean et al 2018). A recent paper used mathematical modelling to further show the importance of horizontal transmission of symbionts among aphids, focusing on the potential of parasitoid wasps to transmit protective symbionts among aphids (Zytynska & Venturino 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we assessed the presence of facultative symbionts using three individuals per colony and contamination from other colonies cannot be completely excluded. Host infection by several facultative symbionts is known to affect host fi tness in different ways dependent on the symbionts involved (Oliver et al, 2006;Łukasik et al, 2013;Tsuchida et al, 2014;Leclair et al, 2016). Specifi c multiple infection patterns could either result in an amplifi cation of the benefi cial effects associated with each symbiont (Oliver et al, 2006) or in severe costs for host aphids (Oliver et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A. gossypii coinfected with Hamiltonella and Arsenophonus displayed enhanced fitness [113]. In contrast, Leclair et al [114] revealed that coinfecting Hamiltonella negatively affected the beneficial phenotype provided by Rickettsiella.…”
Section: Interactions Between Symbiontsmentioning
confidence: 98%